2017
DOI: 10.1038/s41467-017-00231-1
|View full text |Cite
|
Sign up to set email alerts
|

CD206+ M2-like macrophages regulate systemic glucose metabolism by inhibiting proliferation of adipocyte progenitors

Abstract: Adipose tissue resident macrophages have important roles in the maintenance of tissue homeostasis and regulate insulin sensitivity for example by secreting pro-inflammatory or antiinflammatory cytokines. Here, we show that M2-like macrophages in adipose tissue regulate systemic glucose homeostasis by inhibiting adipocyte progenitor proliferation via the CD206/ TGFβ signaling pathway. We show that adipose tissue CD206 + cells are primarily M2-like macrophages, and ablation of CD206 + M2-like macrophages improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
190
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(208 citation statements)
references
References 58 publications
(83 reference statements)
11
190
2
Order By: Relevance
“…Recently, resident CD206 + ATMs were suggested to inhibit adipogenesis and promote adipocyte hypertrophy and insulin resistance [17]. This would fit with our data early in HFD feeding at 7-14d, showing increased resident ATM quantity with no change in PAs (Figure 1E, Supplemental Figure S1).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, resident CD206 + ATMs were suggested to inhibit adipogenesis and promote adipocyte hypertrophy and insulin resistance [17]. This would fit with our data early in HFD feeding at 7-14d, showing increased resident ATM quantity with no change in PAs (Figure 1E, Supplemental Figure S1).…”
Section: Discussionsupporting
confidence: 89%
“…These studies support the importance of M2-like tissue resident ATMs in tissue homeostasis. Indeed, ATMs with M2-like profiles are implicated in regulation of adipocyte hypertrophy and extracellular matrix remodeling, both of which are important for maintaining metabolically healthy adipose tissue [1719]. Thus, phenotypic changes in both CD11c + and resident ATMs with obesity may together strongly influence adipose tissue health and contribute to development of insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Tissues for the western blot analysis were quickly frozen in liquid nitrogen and preserved at −80°C until the analysis. The western blot analysis was performed as described previously . Briefly, the tissues for western blotting were homogenized in lysis buffer containing 25 mM Tris–HCl (pH 7.4), 10 mM Na 3 VO 4 , 100 mM NaF, 50 mM Na 4 P2O 7 , 10 mM EDTA, 0.2% leupeptin (5 mg/mL), 0.5% aprotinin (5 mg/mL), 2 mM phenylmethylsulfonyl fluoride, and 1% Nonidet P‐40, using a Multi‐Beads Shocker cell disrupter (Yasui Kikai Corporation, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…For the intraperitoneal glucose tolerance test, the mice were fasted for 18 h and were administered an intraperitoneal injection of glucose; 1 mg/g body weight (BW). For the intraperitoneal insulin tolerance test, mice fasted for 2–3 h and were administered an intraperitoneal injection of human insulin (0.8 units/kg BW for the mice fed NC and 1.2 units/kg BW for the mice fed HFD . Blood samples were then collected from the tail vein at 0, 15, 30, 45, 60, 90, and 120 min after the injection for glucose/insulin measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Depletion of CD206 + macrophages resulted in an increased number of smaller adipocytes, as well as an amelioration of systemic insulin sensitivity. The results indicated that CD206 + macrophages may contribute to a special niche in adipose tissues which functions to suppress the growth and differentiation of adipocyte progenitors (60). …”
Section: Macrophage Depletion Modelsmentioning
confidence: 99%